PHYSICS LABORATORY - FILÍPEK, Josef (Trends in education, 2008)
The students divided into small working groups are simultaneously working at 11 different work-stations. They work on practical experiments and elaborate the written reports. Individual experiments are completely different and students often do not understand their principles. Group of authors has created an animated manual, which is describing theoretical background as well as practical performace of the experiments.
Keywords: physics; laboratory experiments; interactive animations; elearning